2004
DOI: 10.1016/s1469-0292(02)00049-3
|View full text |Cite
|
Sign up to set email alerts
|

Career transitions in sport: European perspectives

Abstract: Background and purpose Sport psychologists have, since the 1970-1980s, focused their attention on the concept of transitions faced by athletes. While originally described in terms of anecdotal evidence of the process of retirement from high-level competitive and professional sports, the concept of transitions has, during the past decade, become a well delineated topic of study among the sport psychology community. This introductory article provides an overview of the major developments within this thematic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
239
0
65

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(314 citation statements)
references
References 23 publications
10
239
0
65
Order By: Relevance
“…Research in understanding athlete career transitions in sport has commonly focused on preventing negative transition in order to assist elite athletes (e.g., Pearson & Petitpas, 1990), either transitioning out of/within sport (cf., (Sinclair & Orlick, 1993;Stambulova, Stephan, & Japhag, 2007;Wylleman, Alfermann, & Lavallee, 2004; or adjusting to the differences of contextual and structural differences of new competitive levels, often on elite tracks (e.g., Bruner, MunroeChandler, & Spink, 2008;Debois, Ledon, Argiolas, & Rosnet, 2012). This work is important as findings have indicated that negative transitions are often associated with detrimental sport participation outcomes from a sport development perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in understanding athlete career transitions in sport has commonly focused on preventing negative transition in order to assist elite athletes (e.g., Pearson & Petitpas, 1990), either transitioning out of/within sport (cf., (Sinclair & Orlick, 1993;Stambulova, Stephan, & Japhag, 2007;Wylleman, Alfermann, & Lavallee, 2004; or adjusting to the differences of contextual and structural differences of new competitive levels, often on elite tracks (e.g., Bruner, MunroeChandler, & Spink, 2008;Debois, Ledon, Argiolas, & Rosnet, 2012). This work is important as findings have indicated that negative transitions are often associated with detrimental sport participation outcomes from a sport development perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El desarrollo de una carrera deportiva de alto nivel, exige, en general, una década de plena dedicación para obtener la experiencia necesaria en un deporte donde se competirá de cinco a diez años (Wylleman, Alfermann, y Lavallee, 2004). divide la carrera deportiva en diferentes etapas especí cas: iniciación, aprendizaje, comienzo de la competición, competición al máximo nivel y retirada deportiva.…”
Section: Introductionunclassified
“…Os resultados relativos à presença do sistema escolar na vida desportiva dos jovens não apresentaram uma ligação negativa con rmado na literatura por P et al 52 e não corroboram as a rmações de W et al 68 e W e L 69 de que jovens atletas envolvidos no desporto de competição têm di culdade de conciliar estudos e vida desportiva, também em contexto europeu [70][71] . Em contraste com estudos anteriores que associam os clubes sociais de bairro com pouco incentivo ao estudo, os jovens do COP percecionam a importância que os outros (pais, diretores, treinadores) atribuem à escola, veri cando-se um maior comprometimento com a escola.…”
unclassified